High frequency of the PIK3CA H1047L mutation in Indonesian breast cancer across molecular subtypes - Yan Wisnu Prajoko; Didik Setyo Heriyanto; Bayu Tirta Dirja; Susanto Susanto; Vincent Lau; Andrew Nobiantoro Gunawan; Brigitta Natasya Halim; Nur Dina Amalina (PLoS ONE, 2025)
Breast cancer (BC) is a global health concern with significant mortality rates, necessitating a deep understanding of its molecular landscape. Luminal A and B BC, characterized by estrogen receptor (ER) and/or progesterone receptor (PR) positivity, face challenges in endocrine therapy due to acquired resistance, frequently driven by PI3K/AKT/mTOR pathway activation. This study focuses on the frequency of PIK3CA mutations across molecular subtypes BC within the Indonesian population. The study analyzed collected samples from diverse Indonesian regions, representing various islands. Histopathological analysis and immunohistochemistry classified samples into molecular subtypes. Genetic analysis using PIK3CA mutation detection kits revealed a mutation frequency of 32.9%, with 30 (14.5%) samples located in exon 9 and 38 (18.4%) samples in exon 20. Statistical analyses highlighted associations between PIK3CA mutations and molecular subtypes (p = 0.029), with luminal B HER2-negative (40.5%) and luminal A (40.2%) exhibiting the highest mutation rate. A significant association was also observed between the exon location of only mutated PIK3CA samples and age group (p < 0.001), with most of the PIK3CA exon 9 being ≤ 50 years old (72.4%) and PIK3CA exon 20 being > 50 years old. No statistically significant association was observed between the location of PIK3CA mutation (exons 9 and 20) and the breast site, histopathological diagnosis, and molecular subtypes. Comparisons with existing literature and inconsistencies in PIK3CA mutation frequencies across different BC subtypes underline the need for population-specific research. The study emphasizes the importance of assessing PIK3CA mutations in BC management, offering insights for personalized therapies and potential advancements in understanding this complex disease within the Indonesian context.